Imagery perspective among young athletes: Differentiation between external and internal visual imagery - Yu, Q.-H.; Fu, A. S. N.; Kho, A.; Li, J.; Sun, X. H.; Chan, C. C. H. (Journal of Sport and Health Science, 2016)
Purpose: This study aimed to investigate the construct of external visual imagery (EVI) vs. internal visual imagery (IVI) by comparing the athletes' imagery ability with their levels of skill and types of sports. Methods: Seventy-two young athletes in open (n = 45) or closed (n = 27) sports and with different skill levels completed 2 custom-designed tasks. The EVI task involved the subject generating and visualizing the rotated images of different body parts, whereas the IVI task involved the subject visualizing himself or herself performing specific movements. Results: The significant Skill-Level × Sport Type interactions for the EVI task revealed that participants who specialized in open sports and had higher skill-levels had a higher accuracy rate as compared to the other subgroups. For the IVI task, the differences between the groups were less clear: those with higher skill-levels or open sports had a higher accuracy rate than those with lower skill-levels or closed sports. Conclusion: EVI involves the visualization of others and the environment, and would be relevant to higher skill-level athletes who engage in open sports. IVI, in contrast, tends to be more self-oriented and would be relevant for utilization by higher skill-level athletes regardless of sport type.